A curse dark as gold - Bunce, Elizabeth C. (Arthur A. Levine Books : Scholastic Inc., 2008)
Upon the death of her father, seventeen-year-old Charlotte struggles to keep the family's woolen mill running in the face of an overwhelming mortgage and what the local villagers believe is a curse, but when a man capable of spinning straw into gold appears on the scene she must decide if his help is worth the price.